Micro credit, self-help groups (SHGs), and women empowerment - Tapan, Neeta (New Delhi : New Century Publications, 2010)
Study conducted at Ujjain District in Madhya Pradesh, India.
Includes bibliographical references (p. [225]-240) and index.
Keywords: SHG-BANK LINKAGE PROGRAMME (INDIA); MICROFINANCE -- INDIA -- UJJAIN (DISTRICT); WOMEN IN ECONOMIC DEVELOPMENT -- INDIA -- UJJAIN (DISTRICT); RURAL WOMEN -- INDIA -- UJJAIN (DISTRICT) -- ECONOMIC CONDITIONS; SELF-HELP GROUPS -- INDIA -- UJJAIN (DISTRICT)